(3SjGSI GdCNHGQ h CNHGQ SjGSjI (B/s - (3fLGJj, Rjfs; (3OjfjS(B;(3jjjGs ([(3Ohf ecGf(B] :s (3ecJHI GdTQhb GdOhdjI ,s, 2004)
(3hVY gPG GdcJGH eLehYI eJejRI ef GdeDdajf efge h GdJQcjR h fcGjJ h cGKJdjf ghd LGejShf h cGKdjf bQGfchajJT h jSJcTa gPG GdcJGH ef GdPj jDKQ aj GdJZWjI GdUMajI GdSjGSjI h ef GdPj jLH Gf jDKQ ajgG aj GdOhd GdOjebQGWjI h jQGYj cjajI Yed GdEYdGe chSjW aj GdEJUGd Hjf GdMcheI h GdehGWfjf h Hjf eNJda ef jYedhf aj GdSjGSI h GjVG Hjf GdehGWfjf eY HYVges
Keywords: (3GdLeGgjQs; (3GdSjGSIs; (3GdUMGajhfs; (3GdCNHGQs